Upaya Meningkatkan keaktifan Belajar Daring Melalui Model pembelajaran Poblem Based Learning - Taryanti, Taryanti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study is to improve student learning outcomes during online learning in grade III elementary schools at SD Negeri 1 Guno with the Problem Beased Learning learning model during the covid-19 pandemic. This study uses a qualitative descriptive approach with a phenomenological research design. The methods used are questionnaires, interviews and document studies. The data was obtained from the list of grade III students in Theme 3 . The sampling technique used purposive sampling with consideration of the location of the researcher and the respondent. The data analysis technique used an interactive analysis model by Milles and Huberman. The data validity technique used triangulation technique. This study uses indicators, namely constructing knowledge, student involvement in learning and technical constraints.The results showed that the learning process at SD Negeri 1 Guno during the COVID-19 pandemic took place online by providing mentoring or teacher guidance. The teacher carries out the learning process with the stages of planning, implementing, and evaluating. The implementation of online learning causes problems which then encourage efforts to overcome the problems carried out by teachers, students, parents/guardians of students, along with the waka of the curriculum to make the implementation of online learning successful with the Problem Based Learning learning model.